IDENTIFIKASI BANGUNAN YANG BERADA DALAM KAWASAN SEMPADAN SUNGAI MUSI (BANGUNAN STATUS QUO) KOTA PALEMBANG - Putri, Debi Nadia; Sastra, Ahmad Ridho (Jurnal Tekno Global, 2024)
ABSTRACT Palembang City is a city located in South Sumatra Province and has the status as the capital of South Sumatra Province. Palembang City is geographically crossed by the Musi River. The Musi River is iconic in the city of Palembang. This is marked by the direction of development of the Musi River bank area as a tourism area which is regulated in Palembang City Regional Regulation Number 15 of 2012 concerning Regional Spatial Planning (RTRW) of Palembang City for 2012-2032. Along with the development of Palembang City which is marked by increasing development around the banks of the Musi River, areas in the Musi Riverbank area have been used as residences or settlements by residents. This is certainly in conflict with the Regulation of the Minister of Public Works and Public Housing Number 28/PRT/M/2015 of 2015 concerning the Determination of River Border Lines and Lake Border Lines. Article 15 paragraph 1 states that buildings located on the riverbank are declared in "status quo" and need to be regulated by the government so that the riverbank functions properly again. This study aims to identify the number of buildings located in the Musi River area that are included in the Musi River basin using the buffer method. The results of this study obtained that the buildings located in the Musi River basin amounted to 641 buildings spread across 10 (ten) sub-districts located around the Musi River. The sub-district with the most buildings located in the river basin area is Kertapati sub-district with 301 buildings. The sub-district with the fewest buildings in the river basin area is Bukit Kecil sub-district with 7 buildings. Keywords: River Equivalent, Buffer, Status Quo   ABSTRAK Kota Palembang adalah sebuah kota yang terletak di Provinsi Sumatera Selatan dan berstatus sebagai ibukota dari Provinsi Sumatera Selatan. Kota palembang secara geografis dilewati sungai musi. Sungai musi merupakan iconik di kota palembang. Hal ini ditandai dengan diarahkannya pembangunan kawasan tepi sungai musi sebagai kawasan pariwisata yang diatur pada Peraturan Daerah Kota Palembang Nomor 15 Tahun 2012 Tentang Recana Tata Ruang Wilayah (RTRW) Kota Palembang Tahun 2012-2032. Seiring berkembangnya Kota Palembang yang ditandai dengan meningkatnya pembangunan yang ada disekitar bantaran sungai musi mengakibatkan daerah-daerah yang berada di area sempadan sungai musi dijadikan tempat tinggal atau permukiman oleh warga. Hal ini tentunya bententangan dengan Peraturan Menteri Pekerjaan Umum Dan Perumahan Rakyat Nomor 28/PRT/M/2015 Tahun 2015 Tentang Penetapan Garis Sempadan Sungai Dan Garis Sempadan Danau. Pada pasal 15 ayat 1 menyatakan bangunan-bangunan yang terdapat pada sempadan sungai dinyatakan dalam “status quo” dan berlu diberlakukan penertiban oleh pemerintah agar sempadan sungai berfungsi kembali sebagaimana mestinya. Penelitian ini bertujuan untuk mengidentifikasi jumlah bangunan yang berada dikawasan sungai musi yang masuk dalam wilayah sempadan sungai musi dengan menggunakan metode buffer. Hasil peneltian ini memperoleh bangunan yang berada pada kawasan sempadan sungai musi berjumlah 641 bangunan yang tersebar di 10 (sepuluh) kecamatan yang berada di sekitar sungai musi. Kecamatan yang paling banyak memiliki bangunan yang berada dalam kawasan sempadan sungai adalah kecamatan kertapati dengan 301 bangunan. Kecamatan yang paling sedikit memiliki bangunan di kawasan sempadan sungai adalah kecamatan bukit kecil dengan 7 bangunan. Kata Kunci : Sempadan Sungai, Buffer, Status Quo